PENGEMBANGAN MEDIA CERITA BERGAMBAR BERBANTU APLIKASI CANVA PADA MATA PEMBELAJARAN BAHASA INDONESIA KELAS II DI SDN 15 KOTO BESAR - Aprimadedi; Lika Apreasta; Ropi Armia (STKIP Subang, 2024)
This research was based on several problems that researchers encountered, such as teachers only using minimal media, learning that was monotonous and boring without focus, according to students' interest in learning and learning outcomes, not yet implementing creative and fun learning media. The aim of this research is to develop picture story media assisted by the Canva application for class II Indonesian language learning subjects at SDN 15 Koto Besar. This research uses the type of research and development R&D (Research and Development). This research uses the ADDIE model. The ADDIE model is a systematic learning design model. The ADDIE model has five development stages, namely: Analyze, Design, Development, Implementation, Evaluation. The type of data used in this research is qualitative and quantitative. Development of instruments used validation sheets, practicality questionnaires and effectiveness instruments. Data collection techniques use interviews and documentation. The data analysis techniques used are validity analysis, practicality analysis and effectiveness analysis. Based on the results obtained from three analyzes by 3 validators, content obtained 62.5%, language 87.5% and graphics 93.3%, the categories obtained from these 3 sections were said to be valid and very valid. Then the practicality results for smart card learning media were 87.5% in the very practical category. Based on the results of the effectiveness test of picture story media which used a learning test in the form of questions consisting of 20 multiple choice questions, the average effectiveness was 75.00%. There were 0 students who did not complete. So it is concluded that the picture story media is in the very effective category for use by SDN 15 Koto Baru students in the learning process.